Coming Back to the Absurd: Albert Camus's The Myth of Sisyphus: 80 Years On - Francev, Peter, (Value Inquiry Book Series ;, 2023)
This collection of essays from some of the world's leading Camus scholars is a celebration of the enduring significance and impact of Albert Camus's first philosophical essay The Myth of Sisyphus . Coming Back to the Absurd examines Camus's unique contribution to philosophy through The Myth since its publication. The essays within are intended to engage students and scholars of existentialism, phenomenology and the history of philosophy, as well as those simply seeking greater understanding of one of the most influential philosophers and philosophical constructs of the twentieth century. In revisiting The Myth , the authors hope to inspire a new generation of Camus scholars.